Going and Coming Home in Diasporan Pilgrimage: The Case of Philo's Ἱεροποµποί and Diaspora-Homeland Relations in Alexandrian Jewish Perspective - Trotter, Jonathan R. (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2019)
This article focuses on how community-sanctioned pilgrimage to Jerusalem could be employed to establish both the homeland and the diaspora as places of belonging. As a case study, I will analyze Philo's portrayal of the ἱεροποµποί—a term unique to Philo used to describe those chosen to carry offerings, especially the annual half-shekels—from the diaspora to the Jerusalem temple. I will argue that, according to Philo, the ἱεροποµποί (1) were elected community leaders who functioned as representatives of their communities, (2) enabled those who did not travel to Jerusalem to participate vicariously in sacrifice and pilgrimage, and (3) established both the homeland and the diaspora as places of belonging for their community through providing a context for participating in and perpetuating the collective memory of the Jewish nation, in general, and the Alexandrian Jewish community, in particular.